The Self-Reflective Financial Therapist: Creating a Financial Genogram - Chelsey L. Holden; Michelle Jeanfreau (Journal of Financial Therapy, 2023)
The financial genogram offers the therapist an opportunity to explore and unpack his or her own financial journey as a method of self-reflection and self-discovery as well as to become more responsive and understanding toward our clients. This manuscript utilizes an experiential financial therapy framework to make a case for why this self-of-the-financial-therapist process is beneficial, provides steps on how to create the therapist’s financial genogram, and outlines a guide of reflective questions for the therapist to consider as part of the financial genogram process.
Keywords: financial genogram; self-of-the-therapist; self-reflective therapist; therapist personal growth; financial training